P2X7 Receptor Antagonism Attenuates the Intermittent Hypoxia-induced Spatial Deficits in a Murine Model of Sleep Apnea Via Inhibiting Neuroinflammation and Oxidative Stress - Yan Deng; Xue-Ling Guo; Xiao Yuan; Jin Shang; Die Zhu; Hui-Guo Liu (Chinese Medical Journal, 2015)
Background: The mechanism of the neural injury caused by chronic intermittent hypoxia (CIH) that characterizes obstructive sleep apnea syndrome (OSAS) is not clearly known. The purpose of this study was to investigate whether P2X7 receptor (P2X7R) is responsible for the CIH-induced neural injury and the possible pathway it involves. Methods: Eight-week-old male C57BL/6 mice were used. For each exposure time point, eight mice divided in room air (RA) and IH group were assigned to the study of P2X7R expression. Whereas in the 21 days-Brilliant Blue G (BBG, a selective P2X7R antagonist) study, 48 mice were randomly divided into CIH group, BBG-treated CIH group, RA group and BBG-treated RA group. The hippocampus P2X7R expression was determined by Western blotting and real-time polymerase chain reaction (PCR). The spatial learning was analyzed by Morris water maze. The nuclear factor kappa B (NFκB) and NADPH oxidase 2 (NOX2) expressions were analyzed by Western blotting. The expressions of tumor necrosis factor α, interleukin 1β (IL-β), IL-18, and IL-6 were measured by real-time PCR. The malondialdehyde and superoxide dismutase levels were detected by colorimetric method. Cell damage was evaluated by Hematoxylin and Eosin staining and Terminal Transferase dUTP Nick-end Labeling method. Results: The P2X7R mRNA was elevated and sustained after 3-day IH exposure and the P2X7R protein was elevated and sustained after 7-day IH exposure. In the BBG study, the CIH mice showed severer neuronal cell damage and poorer performance in the behavior test. The increased NFκB and NOX2 expressions along with the inflammation injury and oxidative stress were also observed in the CIH group. BBG alleviated CIH-induced neural injury and consequent functional deficits. Conclusions: The P2X7R antagonism attenuates the CIH-induced neuroinflammation, oxidative stress, and spatial deficits, demonstrating that the P2X7R is an important therapeutic target in the cognition deficits accompanied OSAS.